New joint demosaicing and arbitrary-ratio resizing algorithm for color filter array based on DCT approach - Chung, Kuo-Liang; Yang, Wei-Jen; Yan, Wen-Ming; Fuh, Chiou (IEEE transactions on consumer electronics, 2010)
This paper presents a new joint demosaicing and arbitrary-ratio resizing algorithm for mosaic images. By using the adaptive heterogeneity projection masks and Sobel- and luminance estimation-based (SL-based) masks, more accurate edge information is extracted first. Next, the fully populated green color plane is constructed by using the edge-sensing approach and color difference idea. Instead of interpolating the R and B color planes directly, the green-red color difference plane and green-blue color difference plane are therefore interpolated in order to reduce the estimation error. Next, based on the discrete cosine transform (DCT) technique, the above three constructed planes are resized to the arbitrary sized ones. Finally, the resized red and blue color planes are constructed by using the three resized planes, and then the arbitrary sized full color image is obtained. To the best of our knowledge, this is the first time that such a joint demosaicing and arbitrary-ratio resizing algorithm for mosaic images is presented. Based on twenty-four popular testing mosaic images, the proposed resizing algorithm has better image quality performance when compared with three native algorithms which are the combinations of three well-know demosaicing methods and one existing resizing method. Thus, the proposed algorithm can be used in consumer electronic products, such as digital cameras and digital camcorders, to provide the quality-efficient arbitrary-ratio resizing effect.